Pengembangan Video Pembelajaran pada Mata Pelajaran Alat dan Mesin Pertanian di SMK Negeri 4 Gowa - Saleh, Auliah Alifa Azzahra; Sukainah, Andi; Rahman, Khaidir (Agricultural Technology Education Study Program, 2024)
This study is designed to develop and analyze the level of validation, student learning outcomes, and student responses to the use of video learning media. This research refers to research and development (R&D) using the ADDIE development model. The object of research is a learning video media product that was tested to 20 students in small groups, 2 media experts and 2 teaching material experts who evaluated and provided input related to learning video media and instruction books related to video material or content. The study response consisted of 30 grade X ATPH 3 students in a large group. The results showed that the results of media expert validation were in the